Memorandum by Mr. Sheppard respecting Almoner's work from January to June 1903 - Sheppard, G. F. (1903)
1903 1903 1900s 3 pages Memorandum by Mr. Sheppard respecting Almoner's [work] report to the Board respecting her work from January to June 1903. Earnest attempts are being made throughout the Metropolis to encourage thrift and providence among the poorer classes. In 1895, this Hospital set the example of systematic enquiry into the circumstances of applicants for Medical and Surgical relief, and the hope was entertained that such action would not only tend to the relief of the already over-crowded Out Patients Department, but that a considerable number of those whose circumstances were found to disentitle them to further treatment here, would seek the aid of sick clubs and Provident Associations. Action in a similar direction has been taken by the Poor Law Board. The Guardians of this Parish are satisfied that the giant of indiscriminate Medical relief is an open door to pauperism, and during the last 3 years they have laid down 2 rules viz. 1st that applicants for such relief must, (unless certified to be seriously ill) attend in person before the Committee. and 2nd that, except in cases of actual destitution, the relief granted should be on loan. The result has been a decrease of 50 per cent! The increase of Provident Dispensaries is another agency at work. There are now three of these within easy reach of this Hospital. Has our Hospital joined hands with these agencies? -1- 378/IMSW/A/1/2/41